Exploring pathways to outpatients' satisfaction with health care in Chinese public hospitals in urban and rural areas using patient-reported experiences - Xuanxuan Wang; Jiaying Chen; Bo Burström; Kristina Burström (BMC, 2019)
Abstract Background This study aimed to measure outpatients' general satisfaction with and experiences of different aspects of health care in Chinese public hospitals and to investigate to what extent general satisfaction could be explained by patients' experiences in public hospitals located at urban and rural areas. Methods Data on 4782 outpatients were derived from a patient survey in 9 city-level (urban) and 16 county-level (rural) public hospitals across China in 2016. According to Donabedian's model, questions on patients' experiences were categorized into six aspects under "structure" and "process", with general satisfaction representing "outcome". The Chi-square tests were used to test the differences in patients' experiences and general satisfaction between urban and rural areas. The Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to estimate effects of patients' experiences on general satisfaction. Results Compared with respondents in rural areas, there were significantly higher percentages of respondents in urban areas reporting satisfaction and positive experiences in most aspects. As manifested by the path coefficients in PLS models, the positive effect of professional competence (0.197) on general satisfaction was the most significant in respondents at urban areas, followed by communication and information (0.183), and caring attitudes and emotional support (0.174). Among respondents at rural areas, the positive effect of environment facilities (0.199) was the most significant, followed by caring attitudes and emotional support (0.188), and professional competence (0.179). The PLS models explained 44.9 and 46.0% of variations in patient satisfaction at urban and rural areas, respectively. Conclusions Levels of patient satisfaction and experiences at Chinese public hospitals were higher in urban than in rural areas. Outpatients' experiences of professional competence, caring attitudes and emotional support were strongly related to their satisfaction in both settings. However, among respondents in urban areas, experiences of communication and information were more strongly related to satisfaction, whereas among respondents in rural areas, experiences of environment and facilities were more strongly related to satisfaction.